The Use of Theory-Based Formative Research to Design Suicide Prevention Messaging for U.S. Veterans in Midlife. (December 2018) - Karras, Elizabeth; Stokes, Cara M.; Warfield, Sara C.; Elder, Heather; Stephens, Brady; Bossarte, Robert M.
Background . Communication campaigns offer a viable mechanism to promote suicide prevention and reinforce mental health for U.S. veterans in midlife, a group with a high suicide burden. However, little empirical investigation of this type of messaging has been conducted, with formative campaign research conspicuously missing from the limited literature. Aims . Using the theory of planned behavior as a guide, formative research was conducted to inform the design of suicide prevention messaging by (a) describing and measuring several theoretical constructs among our audience and (b) modeling associations between constructs and intentions to seek help for suicidal behaviors and mental health more broadly. Methods . Telephone-based cross-sectional surveys were collected between 2014 and 2016 from a nationally representative sample of veterans with analyses restricted to those aged between 44 and 65 years ( n = 809). Multiple logistic regression was used to identify significant factors associated with intentions to seek help for either suicidal behaviors or mental health. Results . Perceived behavioral control was one of the largest predictors of intentions to seek help for both suicidal behaviors and mental health concerns. Descriptive norms were also significantly associated with suicide-related intentions. Data further suggest several types of attitudes (i.e., discordant beliefs, stereotypes) to consider when designing messages for this group. Discussion . This study represents one of the first efforts to document and describe theoretical constructs and their influence on intentions among veterans in midlife to contribute to the development of evidence-based messaging for veterans informed by a conceptual framework. Conclusion . Findings have important implications as the use of communication strategies for suicide prevention grows increasingly popular.